Preface to Special Issue: Drug Transporters: Regulation and Roles in Therapeutic Strategies - Guofeng You (MDPI AG, 2024)
Drug transporters are membrane proteins, mediating, across cell membranes, the absorption, distribution, and excretion of a diverse array of endogenous and exogenous substances such as nutrients, metabolites, toxins, and drugs [...]